HEALTH PROMOTION OF STAR FRUIT TO LOWER BLOOD PRESSURE IN HYPERTENSION - Prawito Suratman; Karisma Dwi Ana; Aditya Nur Aminudin Azis (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2023)
Educational activities on the use of star fruit to lower blood pressure in hypertension are community service activities. The purpose of this community service is to increase public knowledge about the use of star fruit to lower blood pressure in hypertension. The implementation of community service in Jombatan Village, Kesamben District, Jombang Regency on December 3, 2022. The activities carried out were in the form of education with lecture methods and question and answer discussions. The media used are Audio visual aids and leaflets for educational participants. This activity is prepared about 1 month before it is carried out. Licensing and coordination with the Kesamben Health Center and the Jombatan village government and the implementation time contract are the preparatory stages carried out. The involvement of health cadres and community leaders is carried out in this community service. This activity was attended by 80 residents of Jombatan village. As an evaluation of activities, participants enthusiastically follow the activities to the end and are satisfied with the activities carried out.